2011
DOI: 10.1111/j.1524-475x.2011.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel cholinergic peptides SLURP‐1 and ‐2 regulate epithelialization of cutaneous and oral wounds

Abstract: It is well established that auto/paracrine acetylcholine (ACh) is essential for wound epithelialization, and that the mechanisms include regulation of keratinocyte motility and adhesion via nicotinic ACh receptors (nAChRs). Keratinocyte nAChRs can be also activated by non-canonical ligands, such as secreted mammalian Ly-6/urokinase-type plasminogen activator receptor-related protein (SLURP)-1 and -2. In this study, we determined effects of recombinant (r)SLURP-1 and-2 on migration of human epidermal and oral k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…For transfection of CEC with the HuSH-29™ predesigned shRNA plasmids specific for human M 3 and M 4 mAChR subtypes and α3, α7 and α9 nAChR subunit genes, we followed a standard protocol described by us in detail elsewhere [28]. Briefly, one day before transfection CEC were seeded at a density of 1 × 10 4 cells per well of the 96-well in-cell western (ICW) plates and exposed to experimental, i.e., mAChR subtype-or nAChR subunit gene-specific shRNA or shRNA-NC plasmids in GIBCO™ Opti-MEM I Reduced-Serum Medium (Invitrogen, Carlsbad, CA) with a transfection reagent from Mirus Bio LLC (Madison, WI).…”
Section: Shrna Transfection Experimentsmentioning
confidence: 99%
“…For transfection of CEC with the HuSH-29™ predesigned shRNA plasmids specific for human M 3 and M 4 mAChR subtypes and α3, α7 and α9 nAChR subunit genes, we followed a standard protocol described by us in detail elsewhere [28]. Briefly, one day before transfection CEC were seeded at a density of 1 × 10 4 cells per well of the 96-well in-cell western (ICW) plates and exposed to experimental, i.e., mAChR subtype-or nAChR subunit gene-specific shRNA or shRNA-NC plasmids in GIBCO™ Opti-MEM I Reduced-Serum Medium (Invitrogen, Carlsbad, CA) with a transfection reagent from Mirus Bio LLC (Madison, WI).…”
Section: Shrna Transfection Experimentsmentioning
confidence: 99%
“…Additional evidence for the importance of the ly-6 proteins in epithelial functioning is provided by the work of Grando and co-workers who have shown that slurp-2 stimulated keratinocyte proliferation, migration and inhibited apoptosis, potentially acting through the α3 nAChR [19,39]. By contrast slurp-1 appears to stimulate apoptosis of keratinocytes [40].…”
Section: Nachr-modulatory Ly-6 Proteins In Normal Lungmentioning
confidence: 99%
“…For quantitative real-time (q)PCR, we used primers for α7 (cgcaaccactcaccgtctacttct and cacccctggatattctgacacatt) and α9 (aagtgctgacgaggaata and tgtgactaatccgctctt) nAChR subunits and reaction conditions described by us in the past [40]. The PCR array experiments were performed using the RT 2 -Profiler PCR Array for Human Oncogenes & Tumor Suppressor genes (PAHS-502E, SABiosciences) and ABI Prism 7900 HT (Applied Biosystems, Carlsbad, CA), as detailed by us elsewhere [41].…”
Section: Pcr Experimentsmentioning
confidence: 99%